The librettos of Moniuszko’s operas and the European literary tradition: a comparative perspective on the opposition between serious drama and comedy - Bajer, Michał (Interdisciplinary Studies in Musicology, 2023)
The aim of this study is to indicate several features of serious drama and comedy proper to Moniuszko’s operatic output and to describe them within the context of European points of reference (Pierre de Beaumarchais, Alfred de Musset, Jane Austen, Italian librettists). The network of generic and intertextual relationships shows that an important feature of Moniuszko librettos is not their supposed closure within the circle of national inspiration, but on the contrary – a seemingly insatiable openness to the most valuable areas of foreign legacies. The consistent comparison of comic and serious works in a single study also reveals an affinity between the issues at the heart of Moniuszko’s musical dramas, regardless of the tone of particular works. Moniuszko’s oeuvre, both in its comical and serious aspects, reflects, in different ways, one of the themes that has recurred in Europe after cataclysms, such as the holy wars of the Renaissance, the French Revolution (or the Partitions of Poland during the same period) and the conflicts of the twentieth century. One issue at the core of Polish opera turns out to be the disintegration of the social order and the transition to its opposite – the sudden or gradual, but ineluctable movement from harmony to confusion and violence-filled chaos. Halka and The Pariahforge models of a community based on the exploitation of the weak by the strong. Highlighted are instances of individuals refusing to conform to the anti-order. In the comic variant of Moniuszko’s output, meanwhile (The Haunted Manor, The Countess), the relationship between the order and its contradiction takes on the form of an unjustified renouncing of communal values. At the same time, the comparison between serious and comical works refutes the thesis that Moniuszko was an unequivocal eulogist of an ethics based on the unconditional belonging to a national community.